Analysis of DNA Extraction Protocols for Transgenic Events Determination in Alfalfa - Paz, Florencia Agustina; Parellada, Eduardo Alberto; Coria, María Sumampa; Mondino, Mario Hugo; Palma, Gustavo Adolfo; Cornacchione, Monica (California Alfalfa & Forage Association, Estados Unidos, 2023)
Poster y resumen